Risk of human papillomavirus infection and cervical intraepithelial lesions in Chinese renal transplant recipients - Chen, Ming; Cui, Qiulin; Chen, Meilian; Xia, Meng; Liu, Duo; Chen, Peisong; Wang, Changxi; He, Mian (Frontiers in Oncology, 2022)
Abstract: Objective: While human papillomavirus (HPV) infection in women is associated with cervical intraepithelial neoplasia and cervical cancer, HPV testing is not often performed in routine practice for renal transplantation patients. The genotype-specific prevalence of HPV and risk factors for HPV infection are still unclear. Methods: From 2010 to 2020, patients receiving renal transplantation surgery (referred to as RTRs), who had been screened for HPV infection one year after transplantation were enrolled. A comparison cohort of 4 age- and marital status-matched healthy individuals was selected for RTRs. The clinical characteristics and cervical screening results of RTRs were analyzed. Results: Overall high-risk HPV (hrHPV) infection and abnormal cytology rates in the RTR group were 23.5% and 20.9%, respectively. The odds ratios of hrHPV infection and cervical intraepithelial neoplasia grade 2+ in RTRs vs. non-RTRs were 3.033 (95% CI, 2.013-4.568) and 3.628 (95% CI, 1.863-7.067), respectively. The prevalence of HPV16 in RTRs was much higher (30.4% vs. 8.3%, P=0.002). The multi-infection rate was much higher in HPV-infected RTRs (23.9% vs. 0.1%, P<0.001). The only risk factor for hrHPV infection was the duration of immunosuppression, which increased with time. Conclusion: RTRs had significantly higher HPV infection rates and increased risks of HPV-related cervical premalignancies and cancers due to the immunosuppressed state. Female RTRs may benefit from more frequent cervical cancer screening after renal transplantation than healthy women.